G-Clamp by sand casting / Wan Saiful Azali Wan Ayob, Mohamed Ridzuan Mohamed Rashid and Ahmad Fadzlan Mohamed Shahiri - Wan Ayob, Wan Saiful Azali; Mohamed Rashid, Mohamed Ridzuan; Mohamed Shahiri, Ahmad Fadzlan (2005)
We can use several different methods to shape materials into useful products. Making parts by casting molten metal into a mold and letting it solidify is a logical choice. Indeed, casting is among the oldest methods of manufacturing and was first used in about 4000 B.C to make ornaments, copper arrowheads, and various other objects. In the broad sense, casting is a process that is applied not only to metals but also to nonmetallic materials. Plastics, ceramics, and glasses are also cast into shapes. Basically, metal-casting processes involve the introduction of molten metal into a mold cavity where, upon solidification, the metal takes the shape of the cavity. The casting process is thus capable of producing intricate shapes in a single piece, including those with internal cavities. Very large or hollow parts can be produced economically by casting techniques. Typical cast products are engine blocks, crankshafts, Pistons, valves, railroad wheels, and ornamental artifacts. Although casting processes allow a great deal of versatility in part size and shape, they most often are selected over other manufacturing methods because they: • can produce complex shapes with internal cavities or hollow sections. • can produce very large parts • can utilize work piece materials that are difficult to process by other means. • are economical to use Almost all metals can be cast in (or nearly) the final shape desired, often with only minor finishing required. This capability places casting among important net- shape manufacturing technologies. (Among other similar process is net-shape forging,